2021
DOI: 10.1063/5.0065609
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamics of dielectric droplet collision on different wettability surfaces

Abstract: In this article, we report experimental and semi-analytical findings to elucidate the electrohydrodynamics (EHD) of a dielectric liquid droplet impact on superhydrophobic (SH) and hydrophilic surfaces. A wide range of Weber numbers (We) and electro-capillary numbers (Ca e ) is covered to explore the various regimes of droplet impact EHD. We show that for a fixed We~60, droplet rebound on SH surface is suppressed with increase of electric field intensity (increase of Ca e ). At high Ca e , instead of the usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…As a result, the retraction velocity reduces with increase in E 2 ε. This has been observed in our previous study [21], where rebound suppression on SH surface was observed with increase in electric field intensity for a Newtonian dielectric field. In the present scenario, we have noted that the onset of rebound suppression is largely reduced to lower values of Eo e when the non-Newtonian component is present in the fluids.…”
Section: (B) Droplet Rebound Suppression (Anti-superhydrophobicity) K...supporting
confidence: 86%
See 4 more Smart Citations
“…As a result, the retraction velocity reduces with increase in E 2 ε. This has been observed in our previous study [21], where rebound suppression on SH surface was observed with increase in electric field intensity for a Newtonian dielectric field. In the present scenario, we have noted that the onset of rebound suppression is largely reduced to lower values of Eo e when the non-Newtonian component is present in the fluids.…”
Section: (B) Droplet Rebound Suppression (Anti-superhydrophobicity) K...supporting
confidence: 86%
“…As discussed earlier [21], the dielectric force acting on the droplet is proportional to (E 2 ε). This dielectric force is responsible for elliptic spreading of the droplets.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations